Techniques in molecular biology: polymerase chain reaction (PCR) (multimedia) - Tan, Gin See .
The main propose of this final year project is to produce a creativity,interactive and educational multimedia presentation.The tittle is 'Techniques in molecular biology:poymerase chain reaction'.This multimedia application is designed to be a teaching-learning tool for the convenience of users who prefer learning through self study,or due to handicap or by distance learning.This multimedia work can be used as a reference before the entering lab for doing experiments.The multimedia presentation starts with an introduction and the history of PCR.The defination of PCR is also included.The study of the principles and methods involved is the main scope of the presentation.The users will take note of the important steps that are highligted in the multimedia presentation.Review questions are designed to evaluate the users' understanding of the PCR process.The glosasary and references are provided for the users' convenience.The print notes element is also one of the amenities for the users.The application contains all the multimedia elements such as text,audio,video,graphics and animation.The authoring tools that are used in producing the multimedia presentation are Macromedia Authorware 6.5,Adobe Photoshop 7.0,Ulead GIF Animator 5,Macromedia Flash MX,Microsoft Windows Movie Maker Version 1.1.2427.0,Microsoft Sound Recorder Version 5.1 and ChemDraw Ultra 7.0.Hopefully this piece of work will be useful and interesting to the users.